Semantyka i funkcje barwy czerwonej w Solaris Stanisława Lema - Kaptur, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The article introduces a contribution into the theoretical reflections presented in a series of publications on the names of colours in the poetical output and prose writing of different authors. The author examines the semantic field of the colour that most frequently appears in the novel, its exemplifications in the text and the functions it performs. The article identifies not only hypernyms of the colour red but also non-basic names and hyponyms that refer to the prototypical exemplars of fire and blood. In total, the author analysed 43 primary and secondary names for the colour red exemplified mainly by adjectives and verbs. The collected names of the colour have been assigned to two main thematic circles, i.e. nature (atmospheric phenomena, ocean and its inhabitants) and human being (body, clothes).